2010
DOI: 10.2136/sssaj2009.0440
|View full text |Cite
|
Sign up to set email alerts
|

Managing Runoff Water Quality from Recently Manured, Furrow‐Irrigated Fields

Abstract: Nutrient losses in furrow irrigation runoff potentially increase when soils are amended with manure. We evaluated the effects of tillage, water‐soluble polyacrylamide (WSPAM), and irrigation management on runoff water quality during the first furrow irrigation on a calcareous silt loam soil that had received 45 Mg ha−1 (dry wt.) dairy manure applied in the fall. In Exp. 1, the amended soil was rototilled and irrigated that fall; furrow inflows were either treated with 10 mg L−1 WSPAM injected into furrow inflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…3A and 3B) were 18 to 33% of the 34.8 mg L −1 concentration reported by Lentz and Westermann (2010) in runoff from a recently manured Portneuf soil. In the Lentz and Westermann (2010) study, (i) the manure had been incorporated into dry soil (water contents < 0.05 g g −1 ) just 2 wk before the irrigation, and (ii) little or no microbial activity or leaching had occurred in the manured soil before the irrigation. Thus, water soluble C concentrations in their manured soil were high.…”
Section: Net Dissolved Organic Carbon Lost In Furrow Runoffmentioning
confidence: 73%
See 1 more Smart Citation
“…3A and 3B) were 18 to 33% of the 34.8 mg L −1 concentration reported by Lentz and Westermann (2010) in runoff from a recently manured Portneuf soil. In the Lentz and Westermann (2010) study, (i) the manure had been incorporated into dry soil (water contents < 0.05 g g −1 ) just 2 wk before the irrigation, and (ii) little or no microbial activity or leaching had occurred in the manured soil before the irrigation. Thus, water soluble C concentrations in their manured soil were high.…”
Section: Net Dissolved Organic Carbon Lost In Furrow Runoffmentioning
confidence: 73%
“…Similarly, researchers have studied DOC losses in drainage water, tile-drain, and runoff from grassland soils and corn or hay fields, but did not consider other C-budget components (Don and Schulze, 2008;Royer et al, 2007). Other studies have examined the DOC loadings in surface water inflows and runoff for furrow-or flood-irrigated fields, but did not compare untreated soils with manured soils or measure other C inputs and outputs (Poch et al, 2006;King et al, 2009;Lentz and Westermann, 2010;Mailapalli et al, 2010;Ruark et al, 2010;Krupa et al, 2012).…”
mentioning
confidence: 99%
“…Manure applications are thought to increase the potential for nutrient losses in surface irrigation runoff (Lentz and Westermann 2010). Our findings, however, revealed that the losses of NO 3 -N, NH 4 -N, TP, and FeO P in sprinkler irrigation runoff did not differ for two years between unamended soils and soils into which manure had been applied, then incorporated (table 6).…”
Section: Constituent Loads In Runoff (mentioning
confidence: 49%
“…They found greater TP, DRP, and NH 4 -N concentrations and greater DRP loads in runoff from manure rather than compost plots after amendments were applied for two consecutive years. By delaying irrigation until the spring, one can greatly reduce sediment and nutrient losses in surface irrigation runoff from fields that received manure the preceding fall (Lentz and Westermann 2010). Potassium (K) in runoff is of little environmental concern except when the K is associated with certain anions that increase the salt loading to receiving water bodies.…”
Section: Abstract: Center Pivot-erosion-infiltration-nutrient Lossesmentioning
confidence: 99%
See 1 more Smart Citation